2010
DOI: 10.1371/journal.pone.0015178
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase-III Inhibitor Prevents Hemorrhagic Transformation Induced by Focal Cerebral Ischemia in Mice Treated with tPA

Abstract: The purpose of the present study was to investigate whether cilostazol, a phosphodiesterase-III inhibitor and antiplatelet drug, would prevent tPA-associated hemorrhagic transformation. Mice subjected to 6-h middle cerebral artery occlusion were treated with delayed tPA alone at 6 h, with combined tPA plus cilostazol at 6 h, or with vehicle at 6 h. We used multiple imaging (electron microscopy, spectroscopy), histological and neurobehavioral measures to assess the effects of the treatment at 18 h and 7 days af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 37 publications
7
62
1
Order By: Relevance
“…We determined the optimal timing and route of cilostazol administration in a previous study using a tissue-type plasminogen activator-induced HT model. 12 We have also reported that a high dose of cilostazol (10 mg/kg, IP) suppressed infarct volume, 10 but a lower dose (3 mg/kg, IP) did not, 29 and we found similar results in the present study. However, swelling was exacerbated by warfarin administration, and this effect was suppressed by cilostazol (3 mg/kg, IP), resulting in the same severity of swelling as that seen in the vehicle group.…”
Section: Strokesupporting
confidence: 90%
See 4 more Smart Citations
“…We determined the optimal timing and route of cilostazol administration in a previous study using a tissue-type plasminogen activator-induced HT model. 12 We have also reported that a high dose of cilostazol (10 mg/kg, IP) suppressed infarct volume, 10 but a lower dose (3 mg/kg, IP) did not, 29 and we found similar results in the present study. However, swelling was exacerbated by warfarin administration, and this effect was suppressed by cilostazol (3 mg/kg, IP), resulting in the same severity of swelling as that seen in the vehicle group.…”
Section: Strokesupporting
confidence: 90%
“…26 We and others have reported that cilostazol has protective effects on vascular endothelial cells 10,13,27 and that it suppresses the exacerbation of HT by tissue-type plasminogen activator. 12 In the present study, we obtained the following 4 results: (1) cilostazol (3 mg/kg, IP) prevented the exacerbation of HT caused by warfarin without affecting infarct volume; (2) survival rate was significantly higher in the combination therapy group than in the warfarin monotherapy group; (3) the mechanism whereby cilostazol prevented the exacerbation of HT might involve maintenance of the expression of tight junction proteins (claudin-5 and ZO-1) and VE-cadherin; and (4) combination therapy did not extend bleeding time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations